Effect of CpG-ODN on thymus damage radiated by carbon ions - ZHANG Chao; FU Hua; CAI Jianming; GAO Fu (Fushe yanjiu yu fushe gongyi xuebao, 2021)
To investigate the ameliorative effect of CpG-ODN on thymus damage after carbon ion radiation (CIR), C57BL/6L mice were irradiated with 5 Gy of CIR, and 30-day survival was observed. The index of the thymus was calculated and the degree of thymus damage was evaluated by histological examination. Apoptosis was detected by terminal dexynucleotidyl transferase-mediated dUTP nick and labeling (TUNEL) assay and double-strand break (DSB) was detected by γ-H2AX immunohistochemistry. The number of T cells in the peripheral blood was examined by CD3 antibody labeling. The results showed that CpG-ODN increased mice survival by 50%, obviously ameliorated thymus damage, reduced the number of γ-H2AX foci and TUNEL-positive cells of the thymus, and increased the number of CD3+ T cells in peripheral blood after CIR. This indicated that CpG-ODN could ameliorate thymus damage induced by CIR. These findings might be related to the inhibition of DSB and apoptosis.